Non-noble-metal NiS promoted charge separation and photocatalytic hydrogen evolution for ZnCdS nano-islands on spherical SiO2. (1st April 2023) - Liu, Ke; Yang, Shan; Li, Wei; Wang, Yifan; Sun, Chuanzhi; Peng, Lu; Garcia, Hermenegildo
Highlights: The cheap NiS used as a co-catalyst promotes electron-hole separation and facilitates water adsorption. The structure of special SiO2 /ZnCdS/NiS photocatalyst is beneficial for charge transfer and separation. The hydrogen production activity of SiO2 /ZnCdS/NiS is 2.6 times of SiO2 /ZnCdS/Pt under visible light. Abstract: The efficiency of photocatalytic solar hydrogen evolution closely depends on the charge separation and the effective use of visible light. In this work, a highly efficient photocatalyst SiO2 /ZnCdS/NiS was synthesized through the self-assembly (ZnCdS loading to SiO2 ) and photo-deposition method (NiS loading to ZnCdS). The synergistic effect of SiO2 and NiS NPs can effectively promote photoelectron generation and separation, thereby enhancing photocatalytic performance. The hydrogen production activity of the efficient photocatalyst was as high as 8.4 mmol g -1 h −1 under visible light (λ > 420 nm), 8.4 times of SiO2 /ZnCdS, 4.4 times of ZnCdS/NiS and 2.6 times of SiO2 /ZnCdS/Pt. DFT calculations indicate that NiS, as a catalytic center, is beneficial for electron accumulation and further improves the hydrogen evolution. Meanwhile, loading of NiS to ZnCdS also improves the water adsorption capacity of photocatalyst, which is conducive to photocatalytic water decomposition.